A HALF CENTURY OF THE SONOGASHIRA REACTION - Frankenberger, Stephanie; Wendinger, Dominik; Scherer, Alexander; Sonogashira, Kenkichi; Tykwinski, Rik R.; Hall, Dennis G.; Charette, André (John Wiley and Sons Inc, 2025)
CRIS-Team Scopus Importer:2025-02-28

Laser Desorption Mass Spectrometry of End Group-Protected Linear Polyynes: Evidence of Laser-Induced Cross-Linking - Kirschbaum, Rolf; Prenzel, Dominik; Frankenberger, Stephanie; Tykwinski, Rik; Drewello, Thomas (Journal of Physical Chemistry C, 2015)
End group-protected linear polyynes of composition Tr*-(C C)(n)-Tr* (with Tr* representing the super trityl group and n = 2, 4, 6, 8, 10) and tBu-(C C)(6)-tBu (with tBu being the tertiary butyl group) have been studied by laser desorption ionization (LDI) time-of-flight (ToF) mass spectrometry. tBu-terminated polyyne molecules show considerably higher stability during laser activation than Tr*-end-capped polyyne molecules. A key feature is the abundant formation of oligomeric species upon laser activation. Tandem mass spectrometry reveals strong bonding within the oligomers which indicates cross-linking of the former polyynes within the oligomers. The process is more abundantly occurring and less energy demanding than the laser-induced coalescence of C-60. Cross-linking is more efficient with the smaller end group (tBu), and larger oligomers are formed when the chain length of the polyyne increases, both a result of enhanced interaction of the triple bonds in neighboring chains. The presence of the matrix molecules in matrix-assisted (MA)LDI hinders the polyyne interaction, and oligomer formation is markedly reduced.

Oligomers from sp-Hybridized Carbon: Cumulenes and Polyynes - Frankenberger, Stephanie; Januszewski, Johanna; Tykwinski, Rik (Springer-verlag, 2014)
Carbon-rich organic compounds are candidates for use in a wide range of new technologies. Particularly interesting are materials with a framework of pure carbon, namely the allotropes. Much is known about the most common allotropes, diamond (sp(3)-carbon) and graphite (sp(2-)carbon), as well as the newer allotropes, fullerenes, nanotubes, and graphene. On the other hand, little is known about the allotrope constructed from sp-hybridized carbon atoms, a material commonly called carbyne. Without a defined sample of carbyne to study, synthetic chemists have attempted to model the properties of carbyne through the formation of defined length oligomers based on a cumulene or polyyne skeleton. Spectroscopic analysis of these series of oligomers by vibrational (IR and Raman), NMR, and UV/Vis spectroscopy has outlined some of the potential properties of carbyne. Likewise, X-ray crystallographic analyses give further clues as to the structure of carbyne. This review will highlight selected synthetic methods for cumulenes and polyynes, and it then summarizes characterization data related to structure and bonding in these molecules.
Keywords: Bond length alternation; Carbon allotropes; Cumulenes; Polyynes